Prospective comparison of hypofractionated versus normofractionated intensity-modulated radiotherapy in breast cancer: late toxicity results of the non-inferiority KOSIMA Trial (ARO2010-3) - Sarria, Gustavo R.; Welzel, Grit; Polednik, Martin; Wenz, Frederik; Abo-Madyan, Yasser (Frontiers in oncology, 2022)
PurposeTo compare the late toxicity profile of hypofractionation and normofractionation for whole-breast radiotherapy in breast cancer (BC) patients after conserving surgery.MethodsSixty-year-old or older patients with pTis-pT3, pN0-pN1a, M0 BC were recruited and stratified to hypofractionated (arm R-HF) or normofractionated (arm L-NF) intensity-modulated radiotherapy (IMRT), for right- and left-sided BC, respectively, in this single-center, non-randomized, non-inferiority trial. A boost was allowed if indicated. The primary outcome was the cumulative percentage of patients developing grade III fibrosis, grade I telangiectasia, and/or grade II hyperpigmentation after 2 years, with a pre-specified non-inferiority margin of 15% increase from an expected 2-year toxicity rate of 20%.ResultsThe Median follow-up was 4.93 (0.57-8.65) years for R-HF and 5.02 (0.65-8.72) years for L-NF (p=0.236). The median age was 68 (60-83 and 60-80) years, respectively. In total, 226 patients were recruited (107 for R-HF and 119 for L-NF), with 100 and 117 patients suitable for assessment, respectively. A boost was delivered in 51% and 53% of each arm, respectively. Median PTV volumes were 1013.6 (273-2805) cm3 (R-HF) and 1058.28 (315-2709) cm3 (L-NF, p=0.591). The 2-year primary endpoint rate was 6.1% (95% CI 1.3-11.7, n=5 of 82) and 13.3% (95% CI 7-20.2, n=14 of 105), respectively (absolute difference -7.2%, one-sided 95% CI ∞ to -0.26, favoring R-HF). No local recurrence-free- or overall-survival differences were found.ConclusionIn this prospective non-randomized study, hypofractionation did not have higher toxicity than normofractionated whole-breast IMRT.
Gesehen am 04.11.2022